2021
DOI: 10.29333/ejmste/11248
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Perspectives on Addressing Linguistic Factors Affecting Visualisation of Mathematics Word Problems

Abstract: Visualisation plays a critical role in the teaching and learning of mathematics word problems. It is an essential tool for enabling learners to create meaningful mental pictures necessary for solving mathematical problems. Appropriate visualisation requires good reading skills, English proficiency and an understanding of mathematical vocabulary, language and structure. Although visualisation plays such a critical role, teachers often do not pay attention to linguistic factors when teaching mathematics word pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Reading the problem statement carefully assisted her to identify vital information that led to identifying key symbolic visual mediators. This aligns with Moleko's (2021) study, which found that mathematics teachers use the strategy of highlighting keywords to teach problem-solving and visualization skills.…”
Section: Visual Mediatorssupporting
confidence: 87%
See 2 more Smart Citations
“…Reading the problem statement carefully assisted her to identify vital information that led to identifying key symbolic visual mediators. This aligns with Moleko's (2021) study, which found that mathematics teachers use the strategy of highlighting keywords to teach problem-solving and visualization skills.…”
Section: Visual Mediatorssupporting
confidence: 87%
“…I did not think that the problem was in 3D … (PMT6). Moleko (2021) maintains that reading mathematical word problems without full comprehension can make it difficult to reason and create useful mental images or geometric visual aids for problem-solving. In PMT6's case, her limited ability to visualize, combined with inadequate reading comprehension, led to difficulty in solving the second question in part A of the performance test.…”
Section: Visual Mediatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Making visualizations when proving is crucial because it will produce the desired evidence (VanSpronsen, 2008). Visualization enables students to create meaningful mental images to solve mathematical problems (Moleko, 2021). Making image visualization is an instrumental deconstruction that lays the foundation for problem-solving.…”
Section: Discussionmentioning
confidence: 99%
“…Mathematical word problems can be defined as descriptions of circumstances involving one or more problems that can be solved by performing appropriate mathematical operations on given numerical information (Verschaffel et al, 2010, 2020). As word problems are often presented in everyday contexts, they represent the interaction between mathematics and real life (Moleko, 2021). Solving word problems involves multiple mathematical thinking processes, for example, understanding, planning, calculations and verification (Csíkos & Szitányi, 2019).…”
Section: Introductionmentioning
confidence: 99%